The Russian-Indian Scientific and Technological Cooperation in the First Decade of the 21st Century - Konstantin P. Kurylev; Larisa A. Chereshneva; Mariia N. Starikova; Liudmila A. Belousova (Vestnik RUDN. International Relations)
The article examines the development of the scientific and technical strategic partnership between the Russian Federation and the Republic of India in the first decade of the 21st century. It analyses the main directions, goals and already achieved results of this partnership, as well as prospects for its future. The authors use official documents and materials pertaining to bilateral relations, international Russian-Indian acts, and declarations on scientific, technological cooperation various fields, including exact sciences, biology, biotechnology, oceanography, environmentally friendly technologies, pharmaceuticals, military-technical production, space exploration, and meteorology. They illustrate a diverse array of forms of Russian-Indian cooperation aimed at mutual understanding and progress of both states and peoples. The article is a part of a research project on Soviet-Indian cooperation in the field of science and technology as a resource of the so-called “soft power.” The article’s primary focus is on the distinctive characteristics of the prospects of bilateral cooperation between Russia and India, which commenced in the 20th century, within the context of the cultural and civilizational aspects of international relations system. From a historical perspective, the authors examine the problems of enhancing the effectiveness of cooperation between the two countries at the present stage, given the need for interaction in the scientific, technological, innovative and educational spheres. This is to enable the countries to collectively address the emerging challenges associated with human-induced, climatic and socio-cultural threats, as well as terrorism and religious extremism. The subject is an analysis of the legal framework and content of Russian-Indian cooperation in scientific and technological fields. The constructivist approach is used to study the social processes, which reveal the connection between society and politics, and the influence of international cooperation on the institutionalization and development of scientific and educational cooperation between the USSR/Russia and India at the intergovernmental and interinstitutional levels. When considering the cultural and civilizational specifics of Russia and India, the civilizational and modernization approaches are employed. The authors conclude that the consolidation of the two countries not only strengthens the economic position of Russia and India, but also increases their authority in the international arena. This cooperation between Russia and India is an illustrative example of interstate understanding and friendship in the context of modern geopolitical processes, meeting the national interests of both powers and their respective societies.